Work From Café: Eksplorasi Place Attachment yang Terbentuk pada Pengunjung Kafe di Kota Malang - Thahira, Azia; Sunaryo, Carissa Amelia; Belmondo, Cindy Shabrina; Nina, Damar La; Armalid, Ikhwanul Ihsan (Flourishing Journal, 2025)
The phenomenon of work from café (WFC) has become a new lifestyle among young people, especially university students and freelancers in Malang City. Cafés now serve not only as places to enjoy coffee, but also as alternative public spaces for working, studying, and socializing. This study aims to explore the factors that shape place attachment, or the emotional bond formed by café visitors. A qualitative approach was employed using an exploratory case study design. Four informants were selected through purposive sampling based on their frequency of visits and duration of stay in the cafés. Data were collected through in-depth interviews and observations, then analyzed using Waxman's (2006) framework, which categorizes place attachment into two dimensions: physical and social. The findings show that the most dominant physical factors contributing to place attachment include furniture comfort, adequate lighting, and overall cleanliness. On the social side, the opportunity to linger, a sense of ownership, and feelings of safety and respect contributed most significantly. These findings highlight that both sensory experience and supportive social atmospheres strongly influence visitors’ emotional attachment and loyalty to a café. AbstrakFenomena work from café (WFC) telah menjadi gaya hidup baru di kalangan anak muda, terutama mahasiswa dan pekerja lepas di Kota Malang. Kafe tidak hanya berfungsi sebagai tempat menikmati kopi, tetapi juga sebagai ruang publik alternatif untuk bekerja, belajar, hingga bersosialisasi. Penelitian ini bertujuan untuk mengeksplorasi faktor-faktor pembentuk place attachment yang muncul pada pengunjung kafe. Pendekatan kualitatif digunakan dengan desain studi kasus eksploratif. Sebanyak empat informan dipilih melalui teknik purposive sampling berdasarkan kriteria frekuensi kunjungan dan durasi tinggal di kafe. Data dikumpulkan melalui wawancara mendalam dan observasi, kemudian dianalisis menggunakan teori Waxman (2006) yang membagi place attachment ke dalam dua dimensi: fisik dan sosial. Hasil penelitian menunjukkan bahwa faktor fisik yang paling dominan membentuk place attachment adalah kenyamanan furnitur, pencahayaan yang memadai, dan kebersihan lingkungan. Sementara dari sisi sosial, kenyamanan untuk menetap lama (opportunity to linger), rasa memiliki terhadap tempat (feeling of ownership), dan rasa aman serta dihargai (trust and respect) menjadi ‘’;kontribusi terbesar. Temuan ini menegaskan bahwa pengalaman indrawi dan suasana sosial mempengaruhi loyalitas dan keterikatan emosional pengunjung terhadap sebuah kafe.